The Impact Of Online Misinformation On Covid-19 Vaccines: A Literature Review - Faradita Fradita; Setya Haksama (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2022)
The spread of COVID-19 misinformation has contributed to what has been labelled as a crisis of trust. This decline in trust has been reinforced by legitimate criticism of government responses to the pandemic and the exacerbation of pre-existing mistrust in governments and health services, particularly amongst marginalized groups. This study aims to analyse the COVID-19 vaccines misinformation and its impact to the life aspect of the society. This study was a literature review discussing about COVID-19 vaccines misinformation and its impact. Based on the database and keywords, 15 articles were obtained, but only 7 articles had relevant topics. COVID-19 vaccines misinformation can lead to several impacts namely the damage on the prevention and control action regarding to COVID-19. Moreover, this misinformation also can be as the stimulus undermines the COVID-19 individual responses that will affect the willingness of society’s vaccines uptake. Misinformation of COVID-19 vaccines can be classified into several types such as misleading contents, manipulated content, false content and fabricated content. Those misinformation lead to the condition of society’s acceptance toward COVID-19 vaccines and damage the management of COVID-19 prevention and control actions that are conducted by the Government.